The 13th Conference of the International Sports Engineering Association 2020
DOI: 10.3390/proceedings2020049158
|View full text |Cite
|
Sign up to set email alerts
|

Field Research and Numerical CFD Analysis of Humpback Whale-Inspired Shortboard Fins

Abstract: Compared to other Olympic sports, little research exists on competitive shortboard surfing—especially research comparing field and numerical data. In this paper, GPS sensors with 9-axis motion sensors were used to collect data on nearly 2000 surfed waves. Data were collected from four surfers of differing skill levels, ranging from intermediate/advanced (Level 6) to top-ranked professional (Level 9). The results revealed a positive correlation between surfer skill level and roll/pitch/yaw rates during a cutbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The higher C D these templates report after stall is also an indication of more intense drops in velocity after stall. Shormann et al [18] also discuss the potential board control and recovery benefits of fins with gradual stall behaviour and turbulence damping between the side and centre fins. This observation was also investigated by El-Atm et al [2] when comparing different fin configurations.…”
Section: Template Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher C D these templates report after stall is also an indication of more intense drops in velocity after stall. Shormann et al [18] also discuss the potential board control and recovery benefits of fins with gradual stall behaviour and turbulence damping between the side and centre fins. This observation was also investigated by El-Atm et al [2] when comparing different fin configurations.…”
Section: Template Comparisonmentioning
confidence: 99%
“…It is important to note this study looks at only the yaw motion of a turning surfboard, whereas real-world turning involves a combination of yaw, pitch, and roll [18]. During turns, it is also possible for the fins to not be fully immersed in water, which would affect the forces involved.…”
Section: Shortcomingmentioning
confidence: 99%
“…The same principle can be applied to the lift and drag experienced by fins in surfboards. Several researchers have studied the hydrodynamic performance of three-and four-fin configurations using computational fluid dynamics (CFD) [3,[5][6][7][8][9][10]. It has been shown that the maximum lift for threefin configurations occurred at smaller angle of attached compared to four-fin configurations [6].…”
Section: Introductionmentioning
confidence: 99%